Inhibition of MEK1/2 Signaling Pathway Limits M2 Macrophage Polarization and Interferes in the Dental Socket Repair Process in Mice - Angélica Cristina Fonseca; Priscila Maria Colavite; Michelle de Campos Soriani Azevedo; Daniela Carignatto Passadori; Jessica Lima Melchiades; Rafael Carneiro Ortiz; Camila Oliveira Rodini; Ana Paula Favaro Trombone; Gustavo Pompermaier Garlet (Biology)
Dental socket repair theoretically involves a constructive inflammatory immune response, which evolves from an initial M1 prevalence to a subsequent M2 dominance. In this scenario, the MEK1/2 signaling pathway is allegedly involved in M2 polarization. This study aimed to evaluate the impact of MEK1/2 pharmacological inhibition in the local host response and repair outcome. C57Bl/6-WT 8-week-old male mice were submitted to the extraction of the right upper incisor and treated (or not, control group) with MEK1/2 inhibitor PD0325901 (10 mg/kg/24 h/IP, MEK1/2i group) and analyzed at 0, 3, 7, and 14 days using microcomputed tomography, histomorphometry, birefringence, immunohistochemistry, and PCR array analysis. The results demonstrate that MEK1/2 inhibition limits the development of M2 response over time, being associated with lower expression of M2, MSCs, and bone markers, lower levels of growth and osteogenic factors, along with a higher expression of iNOS, IL-1b, IL-6, and TNF-α, as well inflammatory chemokines, indicating a predominantly M1 pro-inflammatory environment. This modulation of local inflammatory immune response is associated with impaired bone formation as demonstrated by microtomographic and histomorphometric data. The results show that MEK1/2 inhibition delays bone repair after tooth extraction, supporting the concept that M2 macrophages are essential elements for host response regulation and proper repair.